2019
DOI: 10.3390/agronomy9100580
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci (QTL) for Forage Traits in Intermediate Wheatgrass When Grown as Spaced-Plants versus Monoculture and Polyculture Swards

Abstract: It has been hypothesized that the genetic control of forage traits, especially biomass, for grass plants growing as spaced-plants versus swards is different. Likewise, the genetic control of compatibility in grass–legume polyculture mixtures is assumed to be different than for forage production in a grass monoculture. However, these hypotheses are largely unvalidated, especially at the DNA level. This study used an intermediate wheatgrass mapping population to examine the effect of three competition environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…Lazenby and Rogers, 1964;Asay and Johnson 1997;Waldron et al, 2008). This was validated in a recent QTL mapping study of IWG forage traits, where in some cases varying QTL positions and allele effects and were detected for forage biomass and fertile tiller number plant -1 in spaced plant and sward environments (Mortenson et al, 2019). However, whether this persists in more recently developed germplasm for grain and other yield component traits has not yet been published.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Lazenby and Rogers, 1964;Asay and Johnson 1997;Waldron et al, 2008). This was validated in a recent QTL mapping study of IWG forage traits, where in some cases varying QTL positions and allele effects and were detected for forage biomass and fertile tiller number plant -1 in spaced plant and sward environments (Mortenson et al, 2019). However, whether this persists in more recently developed germplasm for grain and other yield component traits has not yet been published.…”
Section: Discussionmentioning
confidence: 66%
“…This suggests that there is limited evidence for a tradeoff between excessive reproductive tillering and yield per spike in spaced plants and again highlights the importance of determining whether excessive tillering is advantageous for yield in a sward environment and if the tendency of a genotype to tiller is stable across these two growing environments. Results from Mortenson et al (2019) suggest relatively low phenotypic and genetic correlations (r p = .10 and r g = .47) between fertile tiller number per plant in IWG spaced plants compared with monoculture sward environments.…”
Section: Crop Sciencementioning
confidence: 90%
See 2 more Smart Citations
“…This finding is supported by the vast differences in GDD accumulation across the two sites (Supplementary Figure S1). Furthermore, previous work in IWG has also shown that the presence and location of QTL can vary depending on whether phenotypic data are tested on an individual environment basis or averaged across environments ( Larson et al 2019 ; Mortenson et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%